Quantitative and Qualitative Traits of Five Local Maize Varieties for Baby Corn Variety Breeding - Rahmawati, Dwi; Santika, Putri; Rizqi, Ainur (Green Engineering Society, 2023)
In Indonesia, the production of baby corn is generally derived from composite varieties because not many varieties have been exclusively bred for baby corn purposes. This study aimed to determine the quantitative and qualitative traits of five local maize varieties to obtain potential parent materials for baby-corn-purposed lines. The research was conducted at the Experimental Field of State Polytechnic Jember using a non-factorial randomized block design with five local maize varieties (‘Kretek Madura’, ‘Bisma’, ‘Provit A1’, ‘Srikandi Kuning’, and ‘Sukmaraga’). The data obtained were analyzed with ANOVA and followed by the Fisher’s Least Significant Difference Test at a 5% error level. The results indicated that all five varieties tested met the standards of Codex for baby corn in terms of diameter, length, and qualitative traits. In terms of plant height, female flowering, and number of ears, V1 ‘Madura Kretek’ was observed to have the most potential as it had the shortest plant height (173.60 cm), the fastest female flowering (43.64 days), and harvest age (47.67 days), as well as the highest number of ears (2.55). However, this variety showed a lower baby corn weight, which might affect the total yield. It is suggested that the next quest of parent material for the baby-corn-purposed line can be also focused on the weight of the baby corn.